Pengaruh Kecepatan Pengadukan Pada Sintesis Biodiesel Dari Minyak Jarak Pagar (Jatropha Curcas L) Dengan Katalis La/Lempung - Yenni Octavia; Syaiful Bahri; Khairat Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The increased energy needs of fossil fuels in particular leads to a decline in the world’s oil reserves which make this extremely rare. One way to reduce the energy crisis and the impact that fossil-funded energy use can have is to develop new and renewable energies such as vegetable fuels. One of the alternative forms of energy currently being developed is biodiesel. Biodiesel is one of the environmentally friendly alternative to diesel fuel. This research studied the effect of agitation speed with variations 300 rpm, 400 rpm 500 rpm, metal that falls into clay with variations 1%, 3%, 5% and activation NaOH with variation 1N, 2N and 3N to the yield biodiesel produced, and to indentifying the characterictics of biodiesel produced. This study begins impregnation of La metal into clay, the La/clay catalyst is calcination for 6 hours at 500oC with N2 gas, oxidation for 2 hours at 400oC with O2 gas and reduction for 2 hours at 400oC with H2 gas. After that, do the process of esterification in the flat bed reactor the temperature reaction 60 oC and reaction time 60 minutes, and then process of transesterification with temperature reaction 60 oC, reaction time 90 minutes, ratio mole oil : methanol 1/9, and catalyst weight 3 % (w/w) oil. Highest biodiesel yield obtained amounted to 89,78 % at the agitation speed 400 rpm and metals La(5%)/clay activation NaOH 3N. Physical characterization of biodiesel were done such as density 884 kg/m3, kinematic viscosity 5.54 mm2/s, acid number 0.676 mg-KOH/g biodiesel and flash point 139 oC respectively which have accordance with the standards of Indonesian biodiesel (SNI 04-7128-2015). Keywords: BBN, biodiesel, esterification, La/Clay catalyst, transesterification